KONSEP DAKWAH DALAM ISLAM - Alimuddin, Nurwahidah (Hunafa: Jurnal Studia Islamika, 2007)
In essence, dakwah means calling people to return to the right path in order that a morally good community is established. In order to achieve this goal, it is necessary to come up with the excellent concept of dakwah, which is supported by its integrated elements. In terms of concept, dakwah should be seen as information, propagation, education and introduction. Meanwhile, the elements include subject of dakwah, as well as its contents and methods.Kata Kunci: Konsep dakwah, penerangan, propaganda, pendidikan dan pengajaran